2007
DOI: 10.1080/02827580701262733
|View full text |Cite
|
Sign up to set email alerts
|

The influence of forest view through a window on job satisfaction and job stress

Abstract: Windows have been found to be a particularly salient feature of the workplace, not only as a matter of preference but also for health and well-being. Depending on what is in the view, looking out of the window may provide numerous opportunities for restoration. This study investigated the effect of window views on job satisfaction and stress. The impact of two specific influencing mechanisms was examined: existence of forest views through windows in workplaces, and absence of forest views through windows in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(62 citation statements)
references
References 21 publications
1
56
0
5
Order By: Relevance
“…In the previous studies, it is reported that natural views from hospital rooms or indoor plants hasten recovery of patients after surgery and decrease systolic blood pressure [27-29]. Those effects in an office location have been studied, showing greater work efficiency and job satisfaction simply by placing indoor plants in the office [30,31]. Furthermore, the higher the stress state, the more effective the nature therapy [32].…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, it is reported that natural views from hospital rooms or indoor plants hasten recovery of patients after surgery and decrease systolic blood pressure [27-29]. Those effects in an office location have been studied, showing greater work efficiency and job satisfaction simply by placing indoor plants in the office [30,31]. Furthermore, the higher the stress state, the more effective the nature therapy [32].…”
Section: Resultsmentioning
confidence: 99%
“…For example, restorative experiences at the workplace can compensate for job resource demands (Bellini et al, 2015a,b). Some studies, in fact, corroborate the hypothesis of a positive restorative effect of the presence of nature in workplaces: views of nature (compared with other views) reduced stress and increased workers’ job satisfaction (Shin, 2007). Furthermore, workers seem to actively look for contact with nature in their work environment.…”
Section: Introductionmentioning
confidence: 81%
“…Several studies conducted in different countries have reported that compared to urban environments, natural environments can better enhance human moods (Hartig, Evans, Jamner, Davis, & GĂ€rling, 2003;Laumann, Garling, & Stormark, 2003;Morita et al, 2006) and work performance (Shin, 2007). In the aspects of physiological responses in nature environments, it is more difficult to control the experimental conditions in the field than in the laboratory.…”
Section: Introductionmentioning
confidence: 99%